Dechlorination of dichlorodiphenyltrichloroethane (DDT) by Fe/Pd bimetallic nanoparticles: Comparison with nZVI, degradation mechanism, and pathways - Ulucan-Altuntas, Kubra; Debik, Eyup (HIGHER EDUCATION PRESS, 2020)
In this study, the bimetallic Fe/Pd nanoparticle was synthesized using the catalytic element palladium to increase the effect of nano zero valent iron (nZVI), in the light of the information obtained from our previous study, in which the nZVI synthesis method was modified. Dichlorodiphenyltrichloroethane (DDT), one of the most widely used persistent organic pollutant pesticides in the world, was investigated in terms of its degradation by Fe/Pd nanoparticles and the difference with nZVI was determined. During the study, the Fe/Pd concentration, initial DDT concentration, and contact time were selected as variables affecting the treatment. The highest possible initial DDT concentration for the treatment with Fe/Pd bimetallic nanoparticle was investigated to obtain the DDT effluent concentration below the carcinogenesis limit, 0.23 mu g/L. The highest concentration that could be treated was found to be 109.95 mg/L with Fe/Pd. It was found that 44.3 min of contact time and 550 mg/L Fe/Pd concentration were needed to achieve this treatment. (C) Higher Education Press and Springer-Verlag GmbH Germany, part of Springer Nature 2019
Keywords: Persistent organic pollutants; nZVI; Bimetallic nanoparticle; Organochlorine pesticides; DDT; ZERO-VALENT IRON; ORGANOCHLORINE PESTICIDE-RESIDUES; FE-PD NANOPARTICLES; CATALYTIC DECHLORINATION; HUMAN-MILK; REMOVAL; WATER; PARTICLES; LINDANE; TETRACYCLINE; Engineering; Environmental Sciences & Ecology